Evaluation of Flowmetry Indicators in Patients with a Wet AMD Form during Antiangiogenic Therapy - N. Yu. Yousef; E. E. Kazaryan; D. M. Safonova; N. Yu. Shkolyarenko; F. B. Dudieva; T. V. Sharnina (Oftalʹmologiâ)
Purpose: to assess the effect of aflibercept (Eylea; “Regeneron”, USA) intravitreal injections on ocular blood flow and intraocular pressure parameters in patients with neovascular form of age-related macular degeneration (wet AMD). Currently, neovascular agerelated macular degeneration (wet AMD) is one of the leading causes of irreversible vision loss and blindness among populations over the age of 50. Material and methods. The study included 35 patients (35 eyes), 10 men and 25 women. Mean patients’ age was 72 ± 6 years. The inclusion criteria were the established diagnosis of a neovascular form of age-related macular degeneration and the level of ophthalmotonus not more than the accepted upper limit of the average norm — IOP 21 mm hg prior to drug administration of the drug. All patients underwent flowmetry with ocular blood flow (OBF) volume determination and intraocular pressure (IOP) measurement. The patients received a singular intravitreal aflibercet injection (2 ml). OBF and IOP were measured at baseline before the injection and the on day 4 and 1 month after the injection. Results. There was no statisticaly significant difference between the IOP level before and after the injection. We revealed a tendency towards OBF decrease in 1 month after the injection, but overall values and the decrease both 4 days and 1 month after the intravitreal injection did not prove to be statistically significant. The absence of statistically significant changes of intraocular pressure level and volumetric ocular blood flow additionally confirms information about the safety of intravitreal administration of aflibercept to patients with a wet form of age-related macular degeneration.